A Great and Sudden Change : Lord Castlereagh, economic reform, and the transformation of post-Napoleonic politics - Parker, Grady Steele (Trinity College (Dublin, Ireland). Department of History, 2014)
Utilizing a political history approach, this thesis presents an account of two distinct, but interrelated narratives of change. Firstly, it presents Castlereagh’s political thought as a process, and seeks to present Castlereagh’s policies as uniquely flexible due to his ends driven political tendencies. The evidence of Castlereagh’s development, on a broad swathe of prominent legislative and ideological debates is then analyzed within the larger context of the second ‘great and sudden change’ brought about by the impact of economic reforms, both supported and opposed by the Liverpool government, in the years that followed the end of the Napoleonic Wars.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin